Al-Haqaiq al-Ijtima'iyyah al-Andalus fi Syi'r Madh wa Tahniah li Ibn Zaydun - Arina Haque; Muhammad Anwar Firdausi; Muhammad Zawawi; Iffat Maimunah (Fakultas Adab dan Humaniora, UIN Syarif Hidayatullah Jakarta, Indonesia, 2022)
PurposeThis study aimed to describe the influence of race, environment, and era in Andalusian society on Ibn Zaidun's hymn (praise) and tahniah (congratulations) poetry using the perspective of Hippolite Adolf Taine. MethodThis study was a qualitative research using a library research design that relied on the hymn and tahniah poetry in Diwan Ibn Zaidun: Rasailuhu, Akhbaruhu, Syi'rul Mikjain written by Kamil Kailani and Abdurrahman. This study analyzed the tradition of praise (madah) and congratulations (tahniah) of the Andalusian community in 19 of Ibn Zaydun's poems communicated with 3 indicators of Taine's theory of social facts, namely race, climate, and time factors. Results/FindingsThis study revealed the influence of the three aspects of Andalusian social facts on Ibn Zaidun's poetry, namely: 1) Ras-Spirit, showing that Andalusian society has the tradition of writing poetry for leaders; 2) Environment-Milieau, that was cool climate surrounded by beautiful green plants have a strong influence on Andalusian Literature, giving rise to many expressions of natural beauty in their poems, especially in praise (madah) and congratulations (tahniah) on Ibn Zaidun's poetry; 3) The Age of Moments privileging Andalusian with many muwashahat, so that the poets paid great attention to rhyme (qafiyah) in their poetry, and the uses of the Andalusian language with Arabic writing became greater in a number of poems. ConclusionAndalusian poetry represented by the poet Ibn Zaydun contains three aspects of Tain social facts. Ibn Zaydun's poetry tradition is influenced by the characteristics of Andalusian society, the climate in the Andalusian city, and the time of writing the poem. The author suggests further studies on the Hypolite Taine social fact theory with its unique scope of social facts. Likewise with Andalusian studies, further studies are urgently needed to find the meaning and social facts behind his classical poems.